The Influence of on the Academic Procrastination of Community Science Polytechnic Cadents - Ibnu Arif Risyat; Kusmiyanti (Ilomata International Journal of Management, 2023)
Starting from excessive use of smartphones and the phenomenon of violations of cadet life regulations regarding careless use of smartphones, the author raised this issue into a scientific article. This article uses quantitative research methods with a population of 345 cadets and a sample of 181 cadets of the 55th Class of Correctional Science Polytechnic using calculations from the Krejci and Morgan sample table. This article finds that there is an influence of Smartphone Addiction on the Academic Procrastination of Correctional Science Polytechnic Cadets. This shows that the more the quality of Smartphone Addiction Cadets increases, the level of Academic Procrastination of the Correctional Science Polytechnic Cadets will also increase. From the results of the Coefficient Test (R2), it is known that the influence of Smartphone Addiction on the Academic Procrastination of Correctional Science Polytechnic Cadets has a percentage of 11.7% and 88.3% is influenced by factors other than Smartphone Addiction. Some of the suggestions given by the author are: Educational Programs on Healthy Smartphone Use, Development of Learning Support Applications, Time Management Skills Workshops, Development of a Supportive Learning Environment, Data Collection and Advanced Research, Collaboration with other institutions, and Tightening Enforcement of Disciplinary Punishments Regarding Use Smartphones. From the results of the Coefficient Test (R2), it is known that the influence of Smartphone Addiction on the Academic Procrastination of Correctional Science Polytechnic Cadets has a percentage of 11.7% and 88.3% is influenced by factors other than Smartphone Addiction.